Collaboration between the Head of Madrasah and the Madrasah Committee to Improve Teacher Performance in the Madrasah Ibtidaiyah Negeri - Maruhawa, Arenibi; Zein, Achyar; Budianti, Yusnaili (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this research work was to analyze the form of communication between the Head of MIN West Medan and the Madrasah Committee at Madrasah Ibtidaiyah Negeri 2 Gunung Sitoli City, analyze the aspects that were communicated by the Head of Madrasah with the Madrasah Committee at Madrasah Ibtidaiyah Negeri 2 Gunung Sitoli, and analyze the communication media used by the Head of Gunung Sitoli City Madrasah Ibtidaiyah Negeri 2. The descriptive method is used in this study, which takes a qualitative approach. The validity of the data collection techniques used interviews, observations, and documentary studies to strengthen the validity of the data found and the authenticity of the research using the standard of data validity suggested by Lincoln and Guba, which consisted of credibility, transferability, dependability, and confirmability. The findings of this study revealed a type of communication between the Head of Madrasah and the Madrasah Committee in Madrasah Negeri 2 Ibtidaiyah Communications that was related to verbal communication between the Madrasah Heads and the Madrasah Committee in Madrasah Ibtidaiyah Negeri 2 Gunung Sitoli